2016
DOI: 10.3389/fpsyt.2016.00179
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Characterization of Psycho-Trauma, Psychological Distress, and Post-traumatic Stress Disorder among Children and Adolescent Internally Displaced Persons in Kaduna, Nigeria

Abstract: BackgroundA postelection violent conflict in Kaduna resulted in 800 deaths and 65,000 displaced people leading to setting up of camp for internally displaced persons (IDPs). We set out to determine the prevalence and pattern of psycho-traumatic stressful life events, psychological distress, and post-traumatic stress disorder (PTSD) among child/adolescents IDPs.MethodsA descriptive cross-sectional study of 73 child/adolescent IDPs were selected by total sampling. Stressful life event checklist measured conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…There are also some differences comparing our data to previous studies with adolescents from the countries included here. For example, PTSD rates found in different Nigerian regions ranged between 2.4 and 9.9% [ 24 , 32 ], while in Brazilian regions between 2.3 and 12.4% [ 33 , 34 ]. In an Indonesian sample, 22.4% of adolescents had PTSD symptoms after a tsunami [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some differences comparing our data to previous studies with adolescents from the countries included here. For example, PTSD rates found in different Nigerian regions ranged between 2.4 and 9.9% [ 24 , 32 ], while in Brazilian regions between 2.3 and 12.4% [ 33 , 34 ]. In an Indonesian sample, 22.4% of adolescents had PTSD symptoms after a tsunami [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance here are collective events such as war trauma, armed conflicts or natural disasters collectively affecting included regions and populations. Fourth, the differences may be due to using different instruments [ 35 ] or semi-structured and diagnostic interviews [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, where historically and currently there have been a wide range of TE and the prevalence of PTSD is thought to range widely between 2.7 and 66.7% [ 43 – 46 ]. Though reasons for such wide range variation in prevalence of PTSD are not known, it is possible that the use of varying study designs, tools and samples studied may have influenced this variation [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though reasons for such wide range variation in prevalence of PTSD are not known, it is possible that the use of varying study designs, tools and samples studied may have influenced this variation [ 47 ]. For example the cross-sectional study reported by Sheikh et al reported a PTSD prevalence of 6.8%, while the case control study of Asuquo et al reported a prevalence of 41.3% [ 43 , 45 ]. Predictors of PTSD in Nigeria include a wide spectrum of events e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation